DETERMINAN MINAT PENGGUNAAN MOBILE BANKING - Dian Lestari (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research aims to analyse the factors influencing individual intentions to use mobile banking. The factors affecting individual intentions to use mobile banking in this research are perceived usefulness, perceived ease to use, anxiety, trust, subjective norm, and perceived behavioral control. This research is a development of previous research that uses a combination of TAM, SCT, and TPB models. Data collection method used is a survey method. The sample is accounting students of Brawijaya University Malang. The data are analyzed using Partial Least Square (PLS). The result shows that anxiety and subjective  norm  affect  individual  intentions  to  use mobile  banking.  However,  the  construct  of perceived usefulness, perceived ease of use, trust, and perceived behavioral control do not affect individual intentions to use mobile banking. The implications of this research are relevant for banking institutions to consider the factors which influence an individual intention to use mobile banking in the development of their information systems.Keywords:  Mobile  banking,  Perceived  Usefulness,  Perceived  Ease  of  Use,  Anxiety,  Trust, Subjective Norm, Perceived Behavioral Control, TAM, SCT, and TPB.